2017
DOI: 10.4157/geogrevjapanb.90.53
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Water Quality as Affected by Water Level Fluctuations in Lake Tonle Sap, Cambodia

Abstract: Lake Tonle Sap has the largest surface area of any lake in Southeast Asia. The lake's water level varied by 8 m between seasons in 2005, which resulted in dramatic seasonal changes in the surface area. The quality of the lake water can be divided into two contrasting types in the low-and high-water-level periods. Measurements of water quality were made during the low-water-level period. Na-HCO 3 type water was a characteristic feature of the water quality in the foreshore areas from March to May of 2005. Of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In shallow lakes with great WLFs, the changes of water quality during a hydrological year were significantly controlled by WLFs (Wantzen et al, 2008; White et al, 2008; Stefanidis and Papastergiadou, 2013). In general, water quality responds immediately to WLFs and was worse with high nutrient concentrations in dry-season than in wet-season, because in dry-season, the lake have a low water capacity for dilution and degradation, low biological consuming of nutrients, and high release of nutrients from sediment to water (Zhu et al, 2013; Yao et al, 2015; Li et al, 2016; Liu X. et al, 2016; Hideo et al, 2017). For PYL particularly, previous studies about the water quality variation associated to WLFs demonstrated high nitrogen concentrations in dry-season (Wu et al, 2006; Yao et al, 2015; Liu X. et al, 2016), compositional changes in DOC related to hydrological regime (White et al, 2008; Yao et al, 2015), and complex distribution patterns of phosphorus (Xiang and Zhou, 2011; Wang and Liang, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In shallow lakes with great WLFs, the changes of water quality during a hydrological year were significantly controlled by WLFs (Wantzen et al, 2008; White et al, 2008; Stefanidis and Papastergiadou, 2013). In general, water quality responds immediately to WLFs and was worse with high nutrient concentrations in dry-season than in wet-season, because in dry-season, the lake have a low water capacity for dilution and degradation, low biological consuming of nutrients, and high release of nutrients from sediment to water (Zhu et al, 2013; Yao et al, 2015; Li et al, 2016; Liu X. et al, 2016; Hideo et al, 2017). For PYL particularly, previous studies about the water quality variation associated to WLFs demonstrated high nitrogen concentrations in dry-season (Wu et al, 2006; Yao et al, 2015; Liu X. et al, 2016), compositional changes in DOC related to hydrological regime (White et al, 2008; Yao et al, 2015), and complex distribution patterns of phosphorus (Xiang and Zhou, 2011; Wang and Liang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated dramatic effects of WLFs on physical properties (e.g., lake morphometry, sedimentation, light penetration, temperature regime, and residence time) (Nowlin et al, 2004; Zohary and Ostrovsky, 2011; Li et al, 2015), chemical environments (e.g., water quality and nutrient distribution and release) (Dinka et al, 2004; Yao et al, 2015; Li et al, 2016; Hideo et al, 2017), and biological populations and communities (e.g., macrophytes, algae, zooplankton, invertebrates, and fish) of lake ecosystems (Coops and Hosper, 2002; Evtimova and Donohue, 2016). In the past decades, natural lakes around the world have been experiencing dramatic changes in their size, morphology, and ecology (Awange et al, 2008), such as the Great Lakes in the United States (Assel et al, 2004; Clites et al, 2014), Lake Chad and Lake Victoria in Africa (Awange et al, 2008; Gao et al, 2011), PYL and Dongting Lake in China (Feng et al, 2012; Yuan et al, 2015; Han et al, 2018), and Lake Tonle Sap in Cambodia (Hideo et al, 2017). As the global climate change and anthropogenic activities increases, extreme WLFs are more frequent and have been becoming one of the main threats impairing the ecological integrity and security of lake ecosystems globally.…”
Section: Introductionmentioning
confidence: 99%
“…DOC, TN, NO 3 − , and SRP had strong effects on microeukaryotic communities in the dry season, while NO 3 − and TP were the key drivers on microeukaryotic community structure in the wet season (Figures 6 and 7). WLFs could control nutrient distribution during a hydrological year in lake ecosystems [12,13]. Water quality usually has fast responses to WLFs with high nutrients concentrations and deterioration in the dry season due to low water capacity, low biological nutrient consumption, as well as high nutrient release from sediment [12,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…WLFs could control nutrient distribution during a hydrological year in lake ecosystems [12,13]. Water quality usually has fast responses to WLFs with high nutrients concentrations and deterioration in the dry season due to low water capacity, low biological nutrient consumption, as well as high nutrient release from sediment [12,[76][77][78]. Previous studies in Poyang Lake revealed that water quality was controlled by WLFs with high nitrogen concentration in the dry season [77,79].…”
Section: Discussionmentioning
confidence: 99%